Comparison between body composition parameters and response to neoadjuvant chemotherapy by using pre-treatment PET CT in locally advanced breast cancer - Inci Kizildag Yirgin; Duygu Has; Gozde Arslan; Esra Cureoglu Aydin; Murat Sari; Semen Onder; Sanli Yasemin; Neslihan Cabioglu; Hasan Karanlik; Mustafa Tukenmez; Memduh Dursun; Mahmut Muslumanoglu; et al. (European Journal of Radiology Open, 2020)
Purpose: To compare the adipose and muscle tissue areas in patients who responded differently to neoadjuvant chemotherapy. Methods: One hundred and eighty six patients diagnosed with breast cancer who underwent neoadjuvant chemotherapy between January 2015- October 2019 and were operated after the treatment were retrospectively included in the study. Pathological results were divided into five groups using the Miller-Payne grading systems. Grade 1 indicating no significant reduction in malignant cells; Grade 2: a minor loss of malignant cells (≤ 30 %); Grade 3: reduction in malignant cells between 30 % and 90 %; Grade 4: disappearance of malignant cells >90 %; Grade 5: no malignant cells identifiable. Pre-treatment PET CT scans were evaluated, and calculation of body composition parameters were performed on a single axial section passing through the L3 vertebrae. Spearman’s correlation test was used to analyze the correlation between SAT, VAT, MT parameters and pathological responses. Results: There was no strong correlation between the 5 groups separated according to neoadjuvant chemotherapy treatment response and tissue distributions. However, that there was a very low correlation found between superficial adipose tissue and pathological response (r=, 156). Conclusion: In conclusion, our results have provided a very low correlation between SAT and more than 30 % response. More research is required to evaluate the role of the body fat and muscle parameters in response to neoadjuvant chemotherapy in larger patient populations.